Manual of techniques in invertebrate pathology - Lacey, Lawrence A., 1946- (Oxford ; Academic Press imprint of Elsevier Science, 2012)
'The second edition of Manual of Techniques in Invertebrate Pathology is written by an international group of experts that contribute a broad array of techniques for the identification, isolation, culture, bioassay, propagation, and storage of the major groups of entomopathogens. The manual provides general and specific background to experienced insect pathologists, biologists, and entomologists who work with pathogen groups that are new to them. It is also useful as a laboratory manual for courses in insect pathology and biological control and related areas of study. Safety testing of entomopathogens in mammals and complementary techniques for the preparation of entomopathogens are included as well as broader methods for the study of specimens such as microscopy and molecular techniques. This manual concentrates primarily on practical step-by-step aspects of the techniques, but also provides the reader with a short history, rationale for usage, guides to supplemental literature, plus recipes for media, fixatives, and stains. Step-by-step instructions for the latest techniques on how to isolate, identify, culture, bioassay and store the major groups of entomopathogensNew edition fully updated to address changes in the taxonomy of the vast majority of taxa Discussion of safety testing of entomopathogens in mammals and also broader methods such as microscopy and molecular techniques Provides extensive supplemental literature and recipes for media, fixatives and stains'--Back cover.
1. Initial handling and diagnosis of diseased invertebrates / L.A. Lacey and L.F. Solter -- 2. Basic techniques in insect virology / Karolin E. Eberle, J$1'Xr(Bg T. Wennmann, Regina G. Kleespies and Johannes A. Jehle -- 3. Isolation, culture, preservation, and identification of entomopathogenic bacteria of the Bacilli / T.W. Fisher and S.F. Garczynski -- 4. Bioassay of bacterial entomopathogens against insect larvae / Maureen O'Callaghan, Travis R. Glare, and Lawrence A. Lacey -- 5. Bacteria for use against soil-inhabiting insects / Albrecht M. Koppenh$1'XZ(Ber, Trevor A. Jackson, and Michael G. Klein -- 6. Identification of entomopathogenic fungi / Richard A. Humber -- 7. Laboratory techniques used for entomopathogenic fungi: Hypocreales / G. Douglas Inglis, Juerg Enkerli, and Mark S. Goettel -- 8. Mass production of entomopathogenic Hypocreales / Stefan T. Jaronski and Mark A. Jackson -- 9. Methods for study of the entomophthorales / Ann E. Hajek, Bernard Papierok, and Jergen Eilenberg -- 10. Preservation of entomopathogenic fungal cultures / Richard A. Humber -- 11. Research methods for entomopathogenic microsporidia and other protists / Leellen F. Solter, James J. Becnel, and Jiri V{u2876}ra -- 12. Nematode parasites, pathogens and associates of insects and invertebrates of economic importance / S. Patricia Stock and Heidi Goodrich-Blair -- 13. Pathogens and parasites of terrestrial molluscs / Michael J. Wilson -- 14. Testing the pathogenicity and infectivity entomopathogens to mammals / Joel P. Siegel -- 15. Complementary techniques: preparations of entomopathogens and diseased specimens for more detailed study using microscopy / James J. Becnel.s
Includes bibliographical references and index.
Keywords: Insects -- Pathogens -- Handbooks, manuals, etc; Invertebrates Pathogens -- Handbooks, manuals, etc; Pathogenic microorganisms -- Handbooks, manuals, etc; Insect pests -- Integrated control -- Handbooks, manuals, etc; Invertebrate pests -- Integrated control -- Handbooks, manuals, etc; Insects -- Diseases